PENGARUH DISIPLIN KERJA DAN PENGAWASAN KERJA TERHADAP EFEKTIVITAS KERJA KARYAWAN PADA PT. ALINDOBAJA PERKASA MEDAN - Rizal P Lubis (Jurnal Abdi Ilmu, 2020)
PT. Aliindobaja Perkasa is a company engaged in Civil & Mechanical Construction Services. The problems in this study, both simultaneously and partially Financial Incentives and Non-Financial Incentives have a positive and significant impact on the work objectives of employees at PT. Sari Surya Officer Medan. The data collection technique in this study was carried out by questionnaires by distributing a list of questions to 43 respondents through the Statistical Product Service Solution (SPSS) Version 18.00 assistance program, From the results of the Fcount test of 187,492 with a significant level of 0.00. Because Fcount 187,492 > Ftable 1.44 and the significant probability is much smaller than 0.05, i.e. 0.00 < 0.05, the regression model can be said that Financial Incentives and Non-Financial Incentives simultaneously have a positive and significant effect on work goals. Based on the test how much influence the independent variables individually on the variables. Test the effect of Financial Incentives on Work Objectives at PT. Sari Surya Perwira Medan tcount 6.865 > ttable1.295 with a significant 0.000 < 0.050, meaning that partially there is a positive and significant effect of Financial Incentives on Work objectives. Sari Surya Perwira Medan tcount 4.130 > ttable 1.295 with a significance of 0.000 > 0.050, meaning that partially there is a significant and significant effect of Non-Financial Incentives on Work Objectives. Determination test (R2), the amount of adjust R square is 0.899, this means that 89.9% of variations in work pleasure can be explained by the independent variables of Financial Incentives and Non-Financial Incentives, while the rest (100% - 89.9% = 10.1%) can be explained by other independent variables. were not included in this study.